The coaching manual : the definitive guide to the process, principles, and skills of personal coaching - Starr, Julie (Pearson Prentice Hall, 2009)
This title combines an understanding of coaching principles, skills, attitudes and behaviours, along with practical guidance and a comprehensive tool kit for coaches.